ON THE RELATIONSHIP BETWEEN THE ORGANOLEPTIC INDICATORS OF MELAMINE AND ITS USE - N.V.Valiev (Web of Journals Publishing, 2024)
This article talks about the use of melamine, its different brands and their organoleptic indicators.
Keywords: Melamine, technology, heavy organic synthesis, chemical industry, materials.